Survey on knowledge and practice of intraoperative temperature management - Md Ralib, Azrina; Mohd Saufian, NorAisyatul Azni; Kamarudin, Norhidayah; Lukman, Mohd Fahmi; Mohamed, Abdul Hadi; Mohd Rus, Razman (2010)
PURPOSE OF STUDY Intraoperative temperature monitoring and management is critically important to prevent complications associated with hypothermia. Satisfactory knowledge and practice in this area amongst the clinicians who are managing the patients intraoperatively is of utmost important to prevent development of hypothermia and its subsequent complications.